Treatment of Refractory Glaucoma by Transscleral Cyclophotocogulation in Micropulse Mode (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Relevance. Neovascular glaucoma (NVG) is one of the most severe forms of secondary glaucoma due to the severe general background and local changes in the form of newly formed vessels in the iris and the anterior chamber angle. A number of diseases can lead to the development of NVG.